Islamic calligraphy in contemporary art of Malaysia / Nor Azlin Hamidon - Hamidon, Nor Azlin (Institute of Graduate Studies, UiTM, 2012)
This research entitled Islamic Calligraphy in Contemporary Art of Malaysia contribute to the most neglected area in the development of the history of art of Malaysia. The combination of three different traditions – Islam, Malay and Western traditions had made significant marks on the form, content and context of the Islamic calligraphy in the Contemporary Art of Malaysia. The objectives of this study are firstly to document contemporary art works of Malaysia that constitutes of Islamic calligraphy. Secondly, is to establish the styles through formal analysis, in terms of its size, medium, techniques, orientation, shape and type of calligraphy. Thirdly, is to uncover the themes of the calligraphy, the sources of quotation and its meanings. Fourthly, is to discover the underlying factors and forces that influence the production of these art works; and finally, to discern the spiritual manifestation from the art works. This study, which covers contemporary art works of Malaysian artists since 1940’s until 2005, managed to give a better picture on aspects that have been neglected by the art historians regarding Islamic and Western impact on the art of Malaysia. In doing so, the researcher is inclining to the theory of Iconology proposed by Erwin Panofsky that covers three levels of analysis, i.e. the pre-iconographical description, iconological analysis and iconographical interpretation.